Economic Policy in Caucasus Region in Assessment of Russian Conservatives: End of 19th - Beginning of 20th Centuries - A. A. Ivanov (Научный диалог)
The article deals with the attitude of Russian conservative (right-wing) publicists to the economic situation in the Caucasus and Transcaucasia during the reign of Emperor Nicholas II. The novelty of the study is seen in the fact that the economic development of the region is firstly considered through the prism of the views of the Russian right-wing movement, always paying special attention to this outskirts of the Russian Empire. The article highlights the right-wing’s views on the influence of the national-religious factor on the economic situation in the Caucasus. It is shown that the conservative circles attached great importance to the economic situation of Russian settlers and measures to raise their number and welfare. Attention is paid to the views of conservative circles on the dominance of foreign companies in the oil industry of the region. It is concluded that the economic policy in the Caucasus and Transcaucasia was considered by the right-wing first of all from the standpoint of nationalism, and their economic ideas were subordinated to political attitudes. It is shown that, being in the right opposition to the national and economic policy of the Russian authorities in the Caucasus, the conservatives were not able to offer detailed alternative programs that can change the situation according to their ideas about the benefits of this region.